ANALISIS KEBERGUNAAN APLIKASI PETUGAS UTBK - Muhammad Riansyah Tohamba; Andi Tenriawaru; LM. Bahtiar Aksara (Simtek : jurnal sistem informasi dan teknik komputer, 2026)
The UTBK Officer Application was developed to support the structured management of examination officers, making interface quality and ease of use critical factors. This study aims to evaluate the usability level of the UTBK officer application within the Halu Oleo University Kendari environment based on three dimensions: task usability, efficiency, and satisfaction. The approach used is a usability questionnaire survey with a Likert scale of 1–5, consisting of 8 closed-ended items and 1 open-ended question, distributed to 879 respondents. Data were analyzed using descriptive statistics, and the reliability of the instrument was tested using Cronbach's Alpha. The results show an overall mean score of 4.55 out of 5, with details of task usability at 4.59, efficiency at 4.48, and satisfaction at 4.52, all of which fall into the "Very Good" category. The Cronbach's Alpha value of 0.949 indicates very high internal consistency of the instrument. Future research is recommended to incorporate user activity logs as an additional data source.